Application of SMS Gateway on Attendance Detection Systems using RFID - Dedi Satria; Taufik Hidayat; M.Aziz Hidayat; Zakaria Zakaria (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
The student attendance monitoring system at school is currently only carried out by the teacher in the form of a student attendance system that is carried out at the beginning of each lesson. And for parents students only get student attendance reports from the final school report. In this case, parental monitoring of student attendance at school on a daily basis cannot be obtained. So it is therefore necessary to have a student attendance detection system that can be monitored remotely. For this reason, the article aims to build a student attendance detection system using RFID that implements sending attendance information to students using SMS to parents of students. The system is built using RFID Tags, RC522 RFID Readers, Arduino Uno and GSM SIM900 modems. The results of the analysis and design of the system, the student attendance detection system has been able to detect the presence of students through RFID tags that are used as student attendance and send attendance information via SMS to parents of students.